Review of the Scorpaena papillosa species complex (Teleostei: Scorpaenidae) with description of a new species from southwestern Australia - Wibowo, Kunto; Motomura, Hiroyuki (Zootaxa, 2020)
A taxonomic review of the Scorpaena papillosa species complex, defined here as having 10 dorsal-fin soft rays, coronal spines, and two upwardly directed spines on the lacrimal bone, resulted in the recognition of two species and two subspecies, Scorpaena papillosa (Schneider & Forster, 1801) including two subspecies, i.e., S. papillosa papillosa (New Zealand) and S. papillosa ergastulorum Richardson, 1842a (southeastern Australia), and S. vesperalis n. sp. (southwestern Australia). Scorpaena p. papillosa and S. p. ergastulorum, are redescribed, with designation of a neotype for S. p. papillosa. Scorpaena vesperalis n. sp., described from coastal waters off southwestern Western Australia on the basis of 57 specimens, is characterized as follows: pectoral-fin rays 14–16; longitudinal scale rows 37–41; body depth 32.3–39.5 % of SL; upper-jaw length 19.6–22.5 % of SL; maxilla depth 5.7–7.3 % of SL; postorbital length 18.2–21.3 % of SL; least distance between interorbital ridges 1.4–2.7 % of SL; 1st anal-fin spine length 7.2–10.0 % of SL; anterior lacrimal spine simple, without additional small spinous points on its posterior margin; a single united pore behind the lower jaw symphysial knob; relatively large supraocular tentacle; all fins of preserved specimens usually uniformly whitish to translucent; and small body size (maximum recorded length 67.6 mm SL). The new species is likely endemic to southwestern Australia. Morphological ontogenetic changes in the relative lengths of some body proportions in the three taxa are also discussed.